The Influence of Tardy Classmates on Students' Socio-Emotional Outcomes. Issue 3 (March 2014) - Gottfried, Michael A.
Background/Context: Researchers, policymakers, and practitioners undoubtedly concur that missing school deteriorates student outcomes. And yet, in evaluating the deleterious effects of missing in-school time, empirical research has almost exclusively focused on absences, and the scant amount of empirical literature on tardiness has focused on academic achievement. Hence, this study contributes novel insight in two capacities: focusing on the effects of tardy classmates and focusing on socio-emotional outcomes. Purpose: The purpose of this study is to determine the effects of peer-level tardiness on individual-level socio-emotional outcomes utilizing nationally representative, longitudinal data. Population/Participants/Subjects: The data are sourced from the Early Childhood Longitudinal Study—Kindergarten Class (ECLS-K), which is a nationally representative sample of students, teachers, and schools. Information was first collected from kindergartners (as well as parents, teachers, and school administrators) from U.S. kindergarten programs in the 1998–1999 school year. This study utilizes data collected at spring of kindergarten, first grade, and third grade. Across all three waves of data, there were a total of N=21, 765 student observations. Research Design: This study combines secondary data analyses and quasi-experimental methods. There are five dependent socio-emotional variables utilized throughout this study, delineated into problem behaviors and social skills. Problem behaviors include two scales: (a) externalizing problem behaviors and (b) internalizing problem behaviors. Social skills include three scales: (a) level of self-control, (b) approaches to learning, and (c) interpersonal skills. This study begins with a baseline, linear regression model. To address issues pertaining to omitted variable bias, this study employs multilevel fixed effects modeling. Findings: The coefficients on classroom tardies indicated statistically significant relationships between having a higher daily average number of classmate tardies and socio-emotional development. Students whose classmates are, on average, tardy more frequently have higher frequencies of problem behaviors and lower levels of social skills. The effects remain significant even after accounting for multiple omitted variable biases. Conclusions/Recommendations: In addition to the previously well-established negative effects of missing school via absences, tardiness also diminishes student outcomes. Hence, the findings in this study—which brought to the surface new ways by which classmates' actions can influence other students' outcomes—would support the continuation of those school practices that successfully reduce multiple channels of missing school. Particularly high rates of peer tardies in addition to high rates of peer absences have both now been established in the research literature as detrimental to individual and classmate outcomes.